Pengembangan Aplikasi Keuangan Excel untuk Meningkatkan Kredibilitas Koperasi Unit Desa Sri Rejeki - Agnisa Widayanti; Gayatria Oktalina (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The Sri Rejeki Village Unit Cooperative (KUD) faces a number of challenges in managing its finances, mainly due to its manual recording system, which is often prone to errors and lacks transparency. Therefore, this study aims to develop an Excel-based financial application to improve accountability and credibility in cooperative financial management. This study employs the Research and Development (R&D) method with a prototype approach, followed by feasibility testing by experts and users. Research data was obtained from three key informants, namely: (1) Nurul Hidayah, M.Sc., as an Accounting Information System Expert, (2) Niken Purnamasari, M.Pd., as a Cooperative Accounting Expert, and (3) Suyitno, Chairman of KUD Sri Rejeki, who acted as the application user. The results of this study indicate that the SIKOP v3 application was successfully developed with key features including transaction recording, financial reporting, and real-time balance monitoring. The application's usability test yielded an average score of 3.6, classified as "Highly Usable," with positive evaluations in terms of functionality, ease of use, and compliance with cooperative accounting standards. The implementation of this application has proven successful in enhancing financial process efficiency, reducing manual errors, and strengthening transparency, ultimately boosting members' trust in the KUD.